Plasma Exosome-Derived SENP1 May Be a Potential Prognostic Predictor for Melanoma - Hu, Hejuan; Ling, Bai; Shi, Yuhan; Wu, Haohao; Zhu, Bingying; Meng, Yiling; Zhang, Guo-Ming (Frontiers in Oncology, 2021)
Objective To evaluate plasma exosome-derived SUMO-specific protease (SENP)1 levels and assess their prognostic value in melanoma. Patients and Methods We extracted exosomes from the plasma of 126 melanoma patients, and identified them with transmission electron microscopy, nanoparticle tracking analysis and western blotting. The plasma exosome-derived SENP1 levels of melanoma patients and healthy controls were detected with ELISA. Results Plasma exosome-derived SENP1 levels in melanoma patients were significantly upregulated than in healthy controls (P < 0.001). Plasma exosome-derived SENP1 levels in melanoma patients with tumor size >10 cm, located in the mucosa or viscera, with Clark level IV/V, with lymph node metastasis, and TNM stages IIb–IV were significantly higher than in patients in with tumor size <10 cm, located in the skin, with Clark level I–III, without lymph node metastasis, and TNM stages IIb–IV (all P < 0.05). Disease-free survival (DFS) and overall survival (OS) were worse in melanoma patients who had higher plasma exosome-derived SENP1 levels than lower plasma exosome-derived SENP1 levels (both P < 0.001). Area under the receiver operating characteristic curve (AUROC) of plasma exosome-derived SENP1 for predicting 3-year DFS of melanoma patients was 0.82 [95% confidence interval (CI): 0.74–0.88], with a sensitivity of 81.2% (95% CI: 69.9–89.6%) and specificity of 75.4% (95% CI: 62.2–85.9%). The AUROC of plasma exosome-derived SENP1 for predicting 3-year OS of melanoma patients was 0.76 (95% CI: 0.67–0.83), with a sensitivity of 95.7% (95% CI: 85.5–99.5%) and specificity of 62.0% (95% CI: 50.4–72.7%). Conclusions Melanoma patients with higher plasma exosome-derived SENP1 levels had worse DFS and OS. The plasma exosome-derived SENP1 levels may be a potential prognostic predictor for 3-year DFS and 3-year OS of melanoma.